Biogenic synthesis of date stones biochar-based zirconium oxide nanocomposite for the removal of hexavalent chromium from aqueous solution. - Hussain, Tauqeer; Akhter, Naheed; Nadeem, Raziya; Rashid, Umer; Noreen, Saima; Anjum, Shazia; Ullah, Sajid; Hussain, Hafiza Raazia; Ashfaq, Aamna; Perveen, Shazia; A. Alharthi, Fahad; Kazerooni, Elham Ahmed (Springer Nature Switzerland AG, 2022)
Pollution of water has become the main problem around the world; chromium (Cr) has several industrial applications. However, Cr is considered very toxic pollutant, because of its carcinogenicity and high toxicity. The existing methods for the treatment of heavy metals are not economical, difficult to operate, and not eco-friendly. The biosorption process is easy to operate, cost effective as well as eco-friendly for the elimination of the toxic metal. In the present work, a zirconium oxide/date stones biochar bio-nanocomposite (ZrO2BNC) was utilized as low-cost biosorbent to remove the toxic Cr (VI). The modification of the activated bio-nanocomposite was confirmed using scanning electron microscopy (SEM), energy-dispersive X-ray (EDX), UV“Vis and Fourier-transform infrared (FTIR) spectroscopy. Optimized condition of various parameters for removal of chromium ion by zirconium oxide bio-nanocomposite (ZrO2BNC) was observed at the pH‰=‰5, contact time 120 min, initial concentration 100 ppm, while 0.1 g sorbent dose. The results showed that the sorption process optimally correlated with Langmuir and 1st kinetic models with R2 value of 0.999. The percentage removal of Cr (VI) ions was checked by atomic absorbance spectrophotometer subsequently before and after the process of adsorption. These findings demonstrated that produced ZrO2BNC can be a cost effective, potential, and novel adsorbent for removel of contaminated chromium metal ions from the aqueous environment.